Factors influencing intra-group data sharing in China’s central state-owned enterprises: An information ecology perspective - Dongxu Wang; Xifeng Ning (PLoS ONE, 2026)
Objectives This paper aims to clarify the factors influencing intra-group data sharing within large central state-owned enterprises (CSOEs) in China, thereby promoting cross-organizational data circulation and sharing. Methods Based on the Stimulus-Organism-Response (SOR) theoretical framework, and integrating Information Ecology Theory and the Theory of Planned Behavior (TPB), this paper develops a research model examining the factors influencing data sharing within CSOEs. Data were collected through a survey questionnaire, yielding 478 valid responses from employees across various CSOEs. Structural Equation Modeling (SEM) was employed to empirically test the research hypotheses. Results (1) Inter-organizational relationship strength and employee data literacy positively influenced both attitude toward data sharing and data sharing intention. (2) Data quality positively influenced intention but had no significant effect on attitude. (3) Data culture and institutional norms exerted a positive influence on both attitude and intention, with institutional norms showing a stronger effect. (4) Data platform integration capability directly influenced data sharing behavior, while platform security assurance capabilities enhanced both intention and behavior. (5) Data sharing intention positively influenced data sharing behavior, but attitude toward data sharing had no significant effect on data sharing intention. Conclusions This study identifies a “Cognitive-Intention Decoupling” phenomenon, and defines the boundary conditions of TPB in the context of strong administrative constraints. It reveals an “Adaptive Reconstruction” mechanism of attitude under strong administrative directives, where organizational normative pressure suppresses the traditional pathway of building internal attitudes based on technological perceptions. Furthermore, the study elucidates the differentiated roles of technological features, finding that platform integration capability acts as a “behavioral shortcut” to bypass intention and directly drive behavior, while data security assurance capability serves as a critical hygiene factor stimulating both intention and behavior.